Pengaruh Absensi Sidik Jari (Finger Print), Kompensasi Dan Produktivitas Terhadap Kinerja Karyawan Pada PT. Sinar Jaya Inti Mulya - Sugeng, Sugeng; Dupri, Muhammad Demsi; Palupi, Kenes Retno (Universitas Muhammadiyah Metro, 2023)
In facing the era of free trade, competition between companies both locally andinternationally is increasing, so Human Resources are needed who have the knowledge,abilities, and skills that can meet the global demand. This forces every company to be able towork more efficiently, effectively, and productively. Human resources (HR) is an essentialaspect of a company. Therefore, a company must be able to manage Human Resources aswell as possible to increase productivity within the company. With good productivity, acompany can meet the company targets that have been set. Good employee performance willhelp employees to meet company targets and also help companies to earn profits. However, ifthe performance of the company's employees decreases, it will be detrimental to thecompany. This study aims to determine the effect of Fingerprint Attendance (Fingerprint), Compensation, and Work Productivity on Employee Performance. This study uses aquantitative approach by using primary data through questionnaires and interviews. Thepopulation in this study was 173 employees. The sample calculation using the Slovin formulaobtained a sample of 121 respondents who were taken through the Simple Random Samplingtechnique. The variables used include Fingerprint Attendance, Compensation, WorkProductivity, and Employee Performance. Analysis of the data used is multiple linearregression with a significance level of 5%. The results of the data test show that theFingerprint Attendance Variablehasa significant positive effect on Employee Performance.The variable of compensation has a significant positive effect on employee performance.Work Productivity variable has a significant positive impact on Employee Performance.Simultaneous F tests together with Fingerprint Attendance, Compensation, and WorkProductivity have a simultaneous effect on Employee Performance.